Effects of Social and Self Stigma on Adolescent Tuberculosis Patients - Nungki Arininta (Faculty of Medicine, Public Health, and Nursing, 2019)
Patient N is 12 years old, suffering from positive AFB pulmonary TB/Tuberculosis (there are 3 microbes in 100 fields of view). This patient has the potential to transmit the disease to others because N does not want to use masks during the intensive phase of TB treatment. This is because the patient is embarrassed and afraid to be excluded fromherfriends. At present, the patient is a freshman in junior high school.The patient lives with both her parents and brother. Her parents worked at odd jobs. Her younger brother is 10 years old. The last education of N's parents were junior high school graduates. This family lives in a house about 100 m2 in size. Some of the cement floors are partly ceramic and brick walls. The condition of the home environment is very windy, so some windows are covered with boards. N sleep in rooms that do not have windows and no glass tiles, so sunlight cannot enter the N's room. The condition of the house is quite clean, but in some rooms, it seems dark, windowless and not exposed to sunlight.